Supramolecular Toxin Complexes for Targeted Pharmacological Modulation of Polymorphonuclear Leukocyte Functions. Issue 17 (18th July 2019) - Heck, Astrid Johanna; Ostertag, Theresa; Schnell, Leonie; Fischer, Stephan; Agrawalla, Bikram Keshari; Winterwerber, Pia; Wirsching, Eva; Fauler, Michael; Frick, Manfred; Kuan, Seah Ling; Weil, Tanja; Barth, Holger
Abstract: The targeted pharmacological modulation of polymorphonuclear leukocytes (PMNs) is of major medical interest. These innate immune cells play a central role in the defense against pathogenic microorganisms. However, their excessive chemotactic recruitment into tissues after traumatic injury is detrimental due to local and systemic inflammation. Rho‐GTPases, being the master regulators of the actin cytoskeleton, regulate migration and chemotaxis of PMNs, are attractive pharmacological targets. Herein, supramolecular protein complexes are assembled in a "mix‐and‐match" approach containing the specific Rho‐inhibiting clostridial C3 enzyme and three PMN‐binding peptides using an avidin platform. Selective delivery of the C3 Rho‐inhibitor with these complexes into the cytosol of human neutrophil‐like NB‐4 cells and primary human PMNs ex vivo is demonstrated, where they catalyze the adenosine diphosphate (ADP) ribosylation of Rho and induce a characteristic change in cell morphology. Notably, the complexes do not deliver C3 enzyme into human lung epithelial cells, A549 lung cancer cells, and immortalized human alveolar epithelial cells (hAELVi), demonstrating their cell type‐selectivity. The supramolecular complexes represent attractive molecular tools to decipher the role of PMNs in infection and inflammation or for the development of novel therapeutic approaches for diseases that are associated with hyperactivity and reactivity of PMNs such as post‐traumatic injury. Abstract : Supramolecular protein complexes comprising of neutrophil‐targeting peptides and the Rho‐inhibiting C3 enzyme are assembled by a "mix‐and‐match" strategy using avidin as a supramolecular "glue." The complexes selectively address primary polymorphonuclear leukocytes (PMNs). The approach holds immense promise to decipher the role of PMNs in infection and inflammation and for diseases that are associated with hyperactivity and reactivity of PMNs.